The Productivity of Economics Departments in the U.S.: Publications in the Core Journals - Conroy, Michael E.; Dusansky, Richard (Journal of Economic Literature, 1995)
The paper ranks Departments of Economics in the U.S., based on publications in a set of eight "Blue Ribbon" journals during the period 1987-91. We adjust for variation in character and page size across the journals, allow for differences in journal quality and deal with changes in department composition over the period by assigning affiliation at the time of assessment rather than at the date of publication. Alternative journal set specifications are examined to test the sensitivity of the composition of the top 25 departments.